2010
DOI: 10.1007/s11557-010-0678-1
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Heterobasidion annosum and Heterobasidion irregulare isolates from central Italy in inoculated Pinus pinea seedlings

Abstract: Five Heterobasidion annosum and five H. irregulare isolates, collected in central Italy, were tested in order to assess the differences in their behaviour, on PDA medium and in two inoculation experiments on three-yearold Pinus pinea seedlings. In vitro the average growth rate of H. irregulare isolates was faster than H. annosum isolates at a temperature ranging between 5 to 30°C. In an inoculation test, performed at a temperature between 8 and 12°C, all the isolates had a comparable growth in the seedlings af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
(17 reference statements)
2
6
0
Order By: Relevance
“…However, there was no difference in the mortality rate of the infected and control seedlings treated by soil infestation. Nevertheless, rates were similar to or even higher than observed by other authors (Lehtijarvi et al 2011;Scire et al 2011), who reported low mortality rates in other pine species, such as P. pinea, P. halepensis, P. nigra, P. sylvestris and P. brutia seedlings. The mortality rates (approximately 35 and 10% for stem inoculation and soil infestation, respectively) were lower than reported for some North American pine species, such as P. elliottii, P. echinata, P. palustris, P. strobus and P. taeda (Delatour et al 1998), and, to a lesser extent, for P. sylvestris (Swedjemark and Stenlid 1995), although inoculation methods were different from those used in this study.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…However, there was no difference in the mortality rate of the infected and control seedlings treated by soil infestation. Nevertheless, rates were similar to or even higher than observed by other authors (Lehtijarvi et al 2011;Scire et al 2011), who reported low mortality rates in other pine species, such as P. pinea, P. halepensis, P. nigra, P. sylvestris and P. brutia seedlings. The mortality rates (approximately 35 and 10% for stem inoculation and soil infestation, respectively) were lower than reported for some North American pine species, such as P. elliottii, P. echinata, P. palustris, P. strobus and P. taeda (Delatour et al 1998), and, to a lesser extent, for P. sylvestris (Swedjemark and Stenlid 1995), although inoculation methods were different from those used in this study.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, seedling mortality did not occur after 3 months from the inoculations, which is consistent with previous findings of maximal mortality rates in young seedlings at between 5 and 14 weeks after inoculation, which was attributed to occlusion of the pathogen from the plant material after this length of time (Swedjemark et al 2001). Indeed, P. pinaster (also called resin pine) produces a large amount of oleoresin (62.8% of resin acids), which acts as mechanical barrier, and monoterpenes (28.7%), which may be fungitoxic (Asiegbu et al 1998;Scire et al 2011). Nevertheless, rates were similar to or even higher than observed by other authors (Lehtijarvi et al 2011;Scire et al 2011), who reported low mortality rates in other pine species, such as P. pinea, P. halepensis, P. nigra, P. sylvestris and P. brutia seedlings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sudden co-occurrence is leading to genetic exchanges between the two taxa, although the European H. annosum is only sporadically present in the habitat colonized by the more assertive American species (Gonthier and Garbelotto 2011). H. irregulare has been suggested to be ecologically more adapted to the Mediterranean climate than the European native species (D'Amico et al 2007;Scirè et al 2011), but pathogenicity on Pinus sylvestris and Pinus pinea appears not to differ between North American, European and introduced North American Heterobasidion isolates . What really differs is the sporulation potential, much higher for the North American species during dry summers .…”
Section: Exotic Host and Pathogen (Fusarium Circinatum)mentioning
confidence: 99%
“…(Rishbeth ; Brown and Webber ; Sciré et al. ) showing an optimum between 20 ° C and 30 ° C and an abrupt decrease in activity above 30°C. Cartwright and Findlay () found a nearly linear response of growth by a number of various decay fungi to temperatures in the range of 3–20 ° C, which is in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%